Identification of potential biomarkers in urine and plasma after consumption of tobacco product in horses. Issue 5 (7th March 2022) - Ishii, Hideaki; Leung, Gary Ngai‐Wa; Yamashita, Shozo; Nagata, Shun‐ichi; Kushiro, Asuka; Sakai, Satoshi; Toju, Kota; Okada, Jun; Kawasaki, Kazumi; Kusano, Kanichi; Kijima‐Suda, Isao
Abstract: The use of nicotine stimulants in horses is generally banned in horse racing and equestrian sports—accidental consumption of tobacco products is one of the possible causes of nicotine exposure in horses. The authors recently reported a comprehensive metabolic study of nicotine in equines, differentiating between nicotine exposure and sample contamination by means of a nicotine biomarker trans ‐3′‐hydroxycotinine. To identify potential biomarkers for the differentiation of genuine nicotine administration and consumption of tobacco products, tobacco leaves (equivalent to 250 mg of nicotine) were nasoesophageally administered to three thoroughbred mares. Quantification methods of anatabine in plasma and urine were newly developed and validated and successfully applied to postadministration samples. Previously reported simultaneous quantification methods of eight target analytes including nicotine and its metabolites in plasma and urine were also applied to the samples. The results demonstrate that both trans ‐3′‐hydroxycotinine and anatabine could be used as potential biomarkers in equine urine and plasma to indicate recent exposure to tobacco products in horses. As well, trans ‐3′‐hydroxycotinine had the longest half‐life as a detectable metabolite in urine and plasma. To our knowledge, this is the first report of a comprehensive study of tobacco product detection in horses. Abstract :